PAPA EST NOMEN IURISDICTIONIS: AUGUSTINUS TRIUMPHUS AND THE PAPAL VICARIATE OF CHRIST - Wilks, M. J. (The journal of theological studies, 1957)
M. J. WILKS; PAPA EST NOMEN IURISDICTIONIS: AUGUSTINUS TRIUMPHUS AND THE PAPAL VICARIATE OF CHRIST, The Journal of Theological Studies, Volume VIII, Issue 1, 1